Energy loss and palsmon excitation during electron emission in the proximity of a solid surface - Gervasoni, Juana Luisa; Arista, Néstor Ricardo (Comisión Nacional de Energía Atómica; Argentina)
Fil: Gervasoni, Juana Luisa Comisión Nacional de Energía Atómica; Argentina